ONTOLOGY MATCHING APPROACH BASED ON TRIANGLE FUZZY EXPRESSION - QIAN, PENGFEI; WANG, YINGLIN (Challenges In Information Technology Management, 2008)
This paper introduces an ontology mapping approach based on triangle fuzzy expression. This approach imports several kinds of similarity fuzzy expressions based on concept feature information. These similarity fuzzy expressions can be used to extend traditional mapping based on name and instance to composite mapping based on name, instance, attribute, taxonomy, dependence and axiom etc. To implement this approach, two questions should be answered: the first is the unification of all kinds of similarity fuzzy expressions and the second is how to realize the composite mapping based on the unified similarity fuzzy expression. The triangle fuzzy expression is regarded as the criterion of the other similarity fuzzy expressions. After the transformation from the other similarity fuzzy expressions to the triangle fuzzy expression, the unified similarity fuzzy expression is realized. Simultaneously, a mapping computation tree is also introduced to finish the whole composite mapping through a series of weight configuration, unification and synthesis. Finally, associated with traditional non-fuzzy mapping approach, the mapping accuracy of this approach will be evaluated through an application example.